Intervertebral Disk Degeneration and Repair. Issue 3 (21st February 2017) - Dowdell, James; Erwin, Mark; Choma, Theodoe; Vaccaro, Alexander; Iatridis, James; Cho, Samuel K
Abstract: Intervertebral disk (IVD) degeneration is a natural progression of the aging process. Degenerative disk disease (DDD) is a pathologic condition associated with IVD that has been associated with chronic back pain. There are a variety of different mechanisms of DDD (genetic, mechanical, exposure). Each of these pathways leads to a final common result of unbalancing the anabolic and catabolic environment of the extracellular matrix in favor of catabolism. Attempts have been made to gain an understanding of the process of IVD degeneration with in Vitro studies. These models help our understanding of the disease process, but are limited as they do not come close to replicating the complexities that exist with an in Vivo model. Animal models have been developed to help us gain further understanding of the degenerative cascade of IVD degeneration In Vivo and test experimental treatment modalities to either prevent or reverse the process of DDD. Many modalities for treatment of DDD have been developed including therapeutic protein injections, stem cell injections, gene therapy, and tissue engineering. These interventions have had promising outcomes in animal models. Several of these modalities have been attempted in human trials, with early outcomes having promising results. Further, increasing our understanding of the degenerative process is essential to the development of new therapeutic interventions and the optimization of existing treatment protocols. Despite limited data, biological therapies are a promising treatment modality for DDD that could impact our future management of low back pain.